2023
DOI: 10.3390/jpm13071093
|View full text |Cite
|
Sign up to set email alerts
|

A Hypertonic Seawater Nasal Irrigation Solution Containing Algal and Herbal Natural Ingredients Reduces Viral Load and SARS-CoV-2 Detection Time in the Nasal Cavity

Abstract: Nasal irrigation is thought to decrease the viral load present in the nasal cavity. Our aim was to assess the effect of a hypertonic seawater solution [with algal and herbal natural ingredients (Sinomarin®)] on the viral load of nasopharynx in patients hospitalized with severe COVID-19 pneumonia. We conducted a prospective, randomized, controlled trial from June 2022 to December 2022. We allocated 56 patients with COVID-19 pneumonia into two groups (28 in each group)—the hypertonic seawater group [nasal irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“… 17 Another study showed that nasal irrigation with 2.3 per cent solution, enriched with brown algae and blue-green algae extracts as well as essential oils of Eucalyptus globulus , Mentha spicata and Thymus vulgaris extracts is a safe and effective method for reducing symptoms of acute viral rhinosinusitis, caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). 18 , 19 This confirmed a previous strategy of successfully using nasal douching solutions in reduction of symptoms of acute viral infection of the upper airway. During irrigation of the nasal cavity with saline solutions, viral particles are mechanically removed.…”
Section: Discussionsupporting
confidence: 79%
“… 17 Another study showed that nasal irrigation with 2.3 per cent solution, enriched with brown algae and blue-green algae extracts as well as essential oils of Eucalyptus globulus , Mentha spicata and Thymus vulgaris extracts is a safe and effective method for reducing symptoms of acute viral rhinosinusitis, caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). 18 , 19 This confirmed a previous strategy of successfully using nasal douching solutions in reduction of symptoms of acute viral infection of the upper airway. During irrigation of the nasal cavity with saline solutions, viral particles are mechanically removed.…”
Section: Discussionsupporting
confidence: 79%
“…However, more research needs to be conducted to determine the correlation between the appropriate temperature and the efficacy of nasal irrigation ( 42 ). There have been investigations conducted on the usage of saline solution in conjunction with other drugs for treating COVID-19 ( 43 , 44 ). Further research needs to be conducted to determine the most effective concentration, temperature, instruments, and positioning of nasal irrigation for the benefit of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 10. Random effects meta-analysis for all RCTs about alkalinization in COVID-19 [119][120][121][122][123][124][125][126]. This plot shows pooled effects, see the specific outcome analyses for individual outcomes, and the heterogeneity section [21] for discussion.…”
Section: Nose/oropharyngeal Treatmentsmentioning
confidence: 99%